2021
DOI: 10.1186/s13195-021-00870-z
|View full text |Cite
|
Sign up to set email alerts
|

Verbal intelligence is a more robust cross-sectional measure of cognitive reserve than level of education in healthy older adults

Abstract: Background Cognitive reserve is most commonly measured using socio-behavioural proxy variables. These variables are easy to collect, have a straightforward interpretation, and are widely associated with reduced risk of dementia and cognitive decline in epidemiological studies. However, the specific proxies vary across studies and have rarely been assessed in complete models of cognitive reserve (i.e. alongside both a measure of cognitive outcome and a measure of brain structure). Complete model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 143 publications
(208 reference statements)
5
27
2
Order By: Relevance
“…With that in mind, we showed that a measure of general cognitive ability taken during young adulthood, but not education, moderated the correlation between memory and hippocampal volume (Vuoksimaa et al, 2013 ). A similar finding has subsequently been shown for current verbal intelligence compared with education (Boyle et al, 2021 ).…”
Section: Implementation In Researchsupporting
confidence: 79%
See 1 more Smart Citation
“…With that in mind, we showed that a measure of general cognitive ability taken during young adulthood, but not education, moderated the correlation between memory and hippocampal volume (Vuoksimaa et al, 2013 ). A similar finding has subsequently been shown for current verbal intelligence compared with education (Boyle et al, 2021 ).…”
Section: Implementation In Researchsupporting
confidence: 79%
“…Given this definition of cognitive reserve, the best available indices, i.e., operational definitions, of cognitive reserve are probably IQ or other measures of general cognitive ability because these essentially measure overall cognitive resources (Boyle et al, 2021 ). Epidemiological studies have found that higher education is associated with reduced risk for dementia (e.g., Zhang et al, 1990 ; White et al, 1994 ; Evans et al, 1997 ; Beydoun et al, 2014 ).…”
Section: Resolving the Inconsistency: Proposed Definitionsmentioning
confidence: 99%
“…Verbal intelligence was a positive predictor of perceptual organization, working memory, processing speed, and executive functions. As already reported by Boyle et al (2021) , verbal intelligence is a more robust cross-sectional measure of CR in comparison to education, occupational complexity, leisure activities, and exercise. These results are in line with the findings of the meta-analysis performed by Opdebeeck et al (2016) , where CR was positively associated with language, memory, working memory, executive function, visuospatial abilities, and general cognition.…”
Section: Discussionsupporting
confidence: 53%
“…Verbal intelligence was used here as CR proxy to assess the face validity of the neuroimaging measure of CR, as it is a robust socio-behavioural proxy of CR (Boyle et al, 2021). Verbal intelligence was measured by the total number of correctly pronounced words on the American National Adult Reading Test (AMNART; Grober & Sliwinski, 1991) in CR/RANN and on an adjusted version of the National Adult Reading Test (NART; Nelson & Willinson, 1982) in TILDA (see Supplemental Information, Methods: Verbal intelligence).…”
Section: Cr Proxymentioning
confidence: 99%